1988
DOI: 10.1002/pd.1970080302
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of chromosome 1 [del(1)(q25q32)] in an infant with prune belly sequence

Abstract: Relatively few cases of deletion 1q have been reported. These cases have been divided into three groups according to assigned breakpoints. They include proximal interstitial, intermediate interstitial, and terminal deletions. We present a male infant with an interstitial deletion of 1q with breakpoints determined by GTG banding as q25 and q32. Comparison with similar case reports suggests common physical features which include microcephaly, growth retardation, developmental delay, clinodactyly, and genital ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The main features seemed to be high forehead; sparse ®ne hair; long philtrum; thin lips; downturned upper lip; low-set, posteriorly rotated ears with anteverted helix; short neck; brachydactyly; and broad thumb/toe. Nevertheless, the facial appearance was not distinctive: our patient resembles the case of Zaletaev et al [1987] and that of Garver et al [1976], but not the case 2 of Taysi et al [1982], who appears similar to the case of Scarbrough et al [1988].…”
Section: Discussionsupporting
confidence: 75%
“…The main features seemed to be high forehead; sparse ®ne hair; long philtrum; thin lips; downturned upper lip; low-set, posteriorly rotated ears with anteverted helix; short neck; brachydactyly; and broad thumb/toe. Nevertheless, the facial appearance was not distinctive: our patient resembles the case of Zaletaev et al [1987] and that of Garver et al [1976], but not the case 2 of Taysi et al [1982], who appears similar to the case of Scarbrough et al [1988].…”
Section: Discussionsupporting
confidence: 75%
“…For example, chromosomal microdeletions involving integrinα3 and duplications of integrinα3 coding regions have been found in patients with intellectual disability (Zahir et al, 2009; Preiksaitiene et al, 2012). Likewise, microdeletions involving genes for integrin β1 (Megarbane et al, 2001; Talkowski et al, 2012), Arg (Scarbrough et al, 1988; Takano et al, 1997; Chaabouni et al, 2006), p190 (James et al, 1996; Leal et al, 2009), and Rho-family GTPases(Newey et al, 2005; Benarroch, 2007) have all been identified in cases of intellectual disability that have been associated with developmental disorders. Mice with mutations in key components of this pathway exhibit defects in dendrite stability and dendritic spine density and morphology that resemble those observed in neurodevelopmental disorders and also exhibit widespread defects in learning, memory, and behavioral flexibility as presented here and in previous studies (Sfakianos et al, 2007; Gourley et al, 2009; Gourley et al, 2012; Warren et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no reported interstitial deletion of the long arm of chromosome 1 that has been characterized by a molecular cytogenetic technique and overlaps the deletion observed in our patient although Mrasek et al [2008] reported a 13.9-Mb familial duplication in 1q31.1-q32.1 in the long arm of chromosome 1 that was present in a father, his mother and his clinically healthy child. All of the published 1q25-q32 deletions have only been characterized using conventional cytogenetic techniques, and 11 patients have been described so far [Garver et al, 1976;Koivisto et al, 1976;Pan et al, 1977;Steinbach et al, 1984;Hamano et al, 1987;Scarbrough et al, 1988].…”
Section: Discussionmentioning
confidence: 99%